Narcissia ahearnae, a new species of sea star from the Western Atlantic (Echinodermata: Asteroidea: Valvatida) - Pawson, David L. (Zootaxa, 2007)
Narcissia ahearnae, new species, is described from off the east coast of Florida and the Bahamas, in depths of 53–135 m. It is distinctive in having conspicuous undulating carinal ridges extending from the center of the disc along the upper surfaces of the arms.